Bulk coarse particle arching phenomena in a moving bed with fine particle presence. Issue 3 (29th January 2014) - Wang, Dawei; Fan, Liang‐Shih
<x xml:space="preserve">Abstract</x> Bridging or arching of flowing solids particles is a serious hazard in the operation of moving bed systems. The mechanics of the arching has been extensively analyzed in the context of particle discharge from a hopper with conical geometry by considering the particulate layer stress distribution. However, bridging can also occur in a moving bed system with cylindrical geometry during the continuous mass flow of solids particles. Experimental work conducted in this study reveals that the appearance of solids bridging is normally accompanied by the presence of fine particles in the coarse moving particles as well as by the countercurrent interstitial gas flow. In this study, a stress analysis of the layered particles distributed in a cylindrical, vertical moving bed that flows downward opposing to upward flow of the interstitial gas is developed to quantify the bridging phenomenon. The analysis takes into account of the effects of presence of fine powder in the coarse particle flows and properties, such as particle‐size distribution, bed voidage, and interstitial gas flow rate. The experimental validation of the present stress analysis for moving bed systems with varied fine and coarse particle concentration distributions, and interstitial gas velocities is also conducted. The stress distributions of the particles under flowing and arching conditions are obtained. An arching criterion is formulated, which indicates that the critical radius of the standpipe to avoid arching phenomenon is only related to the property of the bulk solids in the present geometric configuration of the flow system. © 2014 American Institute of Chemical Engineers AIChE J, 60: 881–892, 2014